2008
DOI: 10.1002/cbic.200800186
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Halogenase of Hormaomycin Biosynthesis for Formation of New Clorobiocin Analogues with 5‐Chloropyrrole Moieties

Abstract: The depsipeptide antibiotic hormaomycin, which is produced by Streptomyces griseoflavus W-384, contains a 5-chloropyrrole moiety. In the producer strain we identified the gene hrmQ that shows sequence similarity to FADH(2)-dependent halogenases. This gene was cloned and heterologously expressed in Streptomyces roseochromogenes var. oscitans DS12.976, which is the producer of the aminocoumarin antibiotic clorobiocin, which contains a 5-methylpyrrole moiety. For the present experiment, we used a mutant of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…If the biosynthetic machinery accepts these modified precursor molecules, modified natural products could arise offering enhanced pharmacological effects and providing new bioorthogonal reactions. Initially some groups proved the integration of halogenases into closely related hosts leading to slightly modified natural products . It is considerably more challenging to incorporate foreign genes into organisms not containing halogenases within the desired biosynthetic pathway.…”
Section: Chemogenetic Early‐stage Halogenation In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…If the biosynthetic machinery accepts these modified precursor molecules, modified natural products could arise offering enhanced pharmacological effects and providing new bioorthogonal reactions. Initially some groups proved the integration of halogenases into closely related hosts leading to slightly modified natural products . It is considerably more challenging to incorporate foreign genes into organisms not containing halogenases within the desired biosynthetic pathway.…”
Section: Chemogenetic Early‐stage Halogenation In Vivomentioning
confidence: 99%
“…Initiallys ome groups provedt he integration of halogenases into closely related hosts leadingt os lightly modified naturalp roducts. [68][69][70] It is considerably more challenging to incorporate foreign genes into organisms not containing halogenases within the desired biosynthetic pathway.T his chemogenetic approach requires that the heterologous hostf acilitates high gene expression levels and correct cellular localizationo ft he halogenase.M oreover,i ti se ssential that the biocatalyst exhibits satisfactory activity and the modified metabolites are sufficientlyt olerated by the biosynthetic machinery.A ccording to this latter approach selected examples are chosen for detailed discussion.…”
Section: Chemogenetic Early-stage Halogenation In Vivomentioning
confidence: 99%
“…All the other flavindependent halogenases, for which in vitro activity could be shown, require a peptidyl carrier protein-tethered substrate (Scheme 37.4) [38,39]. However, it could be shown that by using flavin-dependent halogenases in vivo new products can be obtained [35,[40][41][42]. However, it could be shown that by using flavin-dependent halogenases in vivo new products can be obtained [35,[40][41][42].…”
Section: Lys79mentioning
confidence: 99%
“…This, of course, is extremely limiting to the use of these halogenases for the production of halogenated compounds in an in vitro system. This could be achieved by introducing a different halogenase gene into a strain producing a halogenated compound and thus obtaining a derivative of the normally produced metabolite containing a halogen atom at a different position or a different part of the molecule [35,40,41]. This could be achieved by introducing a different halogenase gene into a strain producing a halogenated compound and thus obtaining a derivative of the normally produced metabolite containing a halogen atom at a different position or a different part of the molecule [35,40,41].…”
Section: Lys79mentioning
confidence: 99%
See 1 more Smart Citation